History and Study of Philosophy of Science in the Development of Value-Based Management Islamic Education - Cahyono, Heri; Iskandar, Iskandar; Setyawati, Eny; Pahrudin, Agus (Graduate Program Magister Manajemen Pendidikan, 2024)
The development of Islamic education management science has become an important aspect in the evolution of knowledge in this domain. The focus of the study involves ontological and epistemological analysis to detail the concept and implementation of management principles in the context of Islamic education. This type of research is qualitative literature research on the History of Philosophy of Islamic Education Science and Management, exploring the evolution of Islamic education management science through literature analysis, combining historical and philosophy of science approaches. The discussion in this research includes four main historical phases and a study of the philosophy of science, with an emphasis on ontology, epistemology and axiology. The basic management concept includes the integration of Islamic values ​​in modern management principles, emphasis on Islamic character, multicultural education, and management of educational quality as well as the role of technology, national standards, and the implementation of the PDCA cycle as a strategy to improve the quality of Islamic education. So, there is a need for in-depth understanding and a holistic approach in overcoming quality challenges in Islamic education.